2004
DOI: 10.1590/s1806-83242004000100012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vinegars on exposure of dentinal tubules: a SEM evaluation

Abstract: Dentin hypersensitivity is a common painful condition observed in clinics. Dietary habits have been much associated with its development and persistence during and following periodontal treatment. The aim of this in vitro study was to evaluate the influence of vinegars on the removal of smear layer and exposure of dentinal tubules. Extracted human teeth were submitted to manual scaling with Gracey curettes in order to remove the cementum as well as to form a smear layer. Dentin samples with 3 mm(2) were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
1
19
0
4
Order By: Relevance
“…Two methods of application were used in the study: Topical application, to simulate the contact between exposed cervical dentin and acidic drinks; and active application, to check if toothbrushing may enhance the erosive effect of dietary acids. 7,12 In this study, the different types of orange juices tested showed different effects on smear layer removal (Graphs 1, 2). Lime orange (pH 5.27) and lime (pH 5.26) had the highest average rank, similar to that of the control group.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Two methods of application were used in the study: Topical application, to simulate the contact between exposed cervical dentin and acidic drinks; and active application, to check if toothbrushing may enhance the erosive effect of dietary acids. 7,12 In this study, the different types of orange juices tested showed different effects on smear layer removal (Graphs 1, 2). Lime orange (pH 5.27) and lime (pH 5.26) had the highest average rank, similar to that of the control group.…”
Section: Discussionmentioning
confidence: 65%
“…Fruit juice was applied to the samples by one of the following methods 7,12 : Topical: Samples were immersed in the juice for 5 minutes and washed with a stream of tap water for 15 seconds. Topical with friction: Samples were immersed in the juice for 5 minutes, manually brushed by the same operator with a soft toothbrush (Colgate, São Bernardo do Campo, SP, Brazil) for 30 sec-• • onds and washed with a stream of tap water for 15 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies evaluated the properties of vinegars on dentin [10,14,15] however, there is no study in the literature evaluating the effect of alcohol and white wine vinegars on microhardness of root dentin.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that vinegars are able to remove smear layer and open dentinal tubules, increasing the permeability and decrease the microhardnesss of the most superficial root canal dentin layer [10,14,15]. Zandim et al [15] observed in vitro that alcohol, apple, rice, white wine and balsamic vinegar were able to remove smear layer and exposure of dentinal tubules, of these, the balsamic vinegar was associated with less removal of smear layer.…”
Section: Introductionmentioning
confidence: 99%